Towards an Acculturation Framework for K-12 Educators who Live and Work Abroad: The Role of Teacher Training Institutions - Rebecca Stroud Stasel (Ali Khorsandi Taskoh, 2021)
The demand for teachers overseas far outweighs the supply. International teachers become sojourners, or "between-society culture travelers" (Ward, et al., 2005, p. 6), but how do they manage to thrive once in their host country? Culture shock presents ubiquitous challenges for teachers. Policyscapes, metaphorical pools of diverse policies converging and sometimes clashing, are sure to add more challenges. This study explored factors affecting teacher thriving overseas. To date, research on expatriate teachers is scarce. Psychological acculturation theories have not covered teachers, which is significant because teachers guide students who are also acculturating. I developed a preliminary educator acculturation framework to inform my three-phase narrative qualitative study on educator acculturation, which explored the experiences of K-12 teachers and school leaders whose educator certification was completed at Anglo-Western institutions of higher education, and who were employed at international schools in Southeast and East Asia, and later sojourning school leaders. This article provides analyses of data from the study's first phase. Findings include evidence of acculturative stress, as well as personal and professional growth from sojourning. Propositions from the study include beginning a scholarly dialogue about educator acculturation, developing an educator acculturation framework, and translating acculturation understandings to praxes by means of reflection and professional development.